Information-seeking behavior of UP College of Law students - Implica, Merry Joy S.; Aguirre, Vyva Victoria M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
We are in the digital era where information can be acquired anywhere. The emergence of the Internet somehow might change the information-seeking behavior of the society. Information-seeking behavior is actions done by a person when in need of information. This study aims to have a better understanding of the information-seeking behavior of UP College of Law students. This study also intends: to determine the techniques used by UP Law students when seeking information; to know if there is a relationship between the students personal characteristics and their preferred techniques in the following information seeking phases: Starting, Chaining, Browsing, Differentiating, Monitoring, Extracting, Verifying and Ending (Ellid, 1998); to determine the issues and concerns encountered by the students in accessing the library; and to ascertain the different ways by which the UP Law Library Management addresses the problems encountered by the students. This study employed survey questionnaire. Two hundred questionnaires were distributed to UP Law students but only 157questionnaires were returned.
From the data gathered, this study found out that during the starting techniques, majority of the respondents frequently consulted the Internet in identifying sources of interest, followed by databases/OPAC. Internet is frequently used by the students because it is accessible and efficient to use during information retrieval.
The students follow up on footnotes when doing the chaining techniques and look at titles of the source when searching for related information for their topic search. They also consider the the quality of information in determining and deciding which materials to use or to reject.
In addition, in finding latest development in areas of interest the students consult their colleagues or peers. The students also include the Internet which yields significant numbers. It only shows that the Internet helps them to be updated on new developments on their topics of interest.
The extracting techniques of the respondents show that they use the Internet when they have found the information source that is most appropriate to their topic of interest. Lastly, the respondents tend to review the materials and their search is already completed when they are satisfied with the information they have gathered.
Majority of the respondents frequently use the Internet, database/OPAC and electronic journals or resources. But, in spite of the emergence of electronic resources, majority of the respondents still prefer print format materials to electronic materials.
This study also found out that the respondents give least attention to library materials such as library bulletin boards, indexes, periodical index, lists etc. though these materials could be helpful in their search.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) College of Law -- Students; Information services -- Use studies -- Philippines -- Quezon City